Optimizing whole-body MRI for early cancer detection in Li-Fraumeni syndrome: a prospective bicentric study - Keymling, Myriam; Kurz, Felix T.; Kuder, Tristan Anselm; Bickelhaupt, Sebastian; Hielscher, Thomas; Hog, Robert; Mokry, Theresa; Moher Alsady, Tawfik; Schott, Sarah; Kratz, Christian Peter; Renz, Diane Miriam Esther; Schlemmer, Heinz-Peter (European radiology, 2025)
Annual whole-body MRI (WB-MRI) is recommended for early cancer detection in individuals with Li-Fraumeni syndrome (LFS). However, there is no agreement on a standardized MRI protocol. This study evaluated the diagnostic performance of different MRI sequences to suggest an optimized protocol for LFS surveillance.
Gesehen am 13.02.2026